The effect of stroke on the bone mineral density: A systematic review and meta-analysis - Jun Wang; Yanshan Sun; Xiang Guo; Zhen Zhang; Hanguang Liang; Tong Zhang (Elsevier, 2024)
Objectives: Stroke survivors frequently encounter physical complications. This study aimed to evaluate the impact of stroke on bone mineral density (BMD) and assess the risk of post-stroke osteoporosis or osteoporotic fractures. Design: Systematic review and meta-analysis. Setting and Participants: We systematically searched Medline, Embase, and the Cochrane Database of Systematic Reviews to identify longitudinal studies reporting the influence of stroke on BMD, osteoporosis, and osteoporotic fractures. Pooled analyses were performed utilizing random-effects models. Results: This study included 21 studies with 1,029,742 participants. The mean difference of BMD in the paretic femoral neck between follow-up and initial measurements was −0.07 g/cm2 (95% CI, −0.09 to −0.04), and −0.03 g/cm2 (95% CI, −0.05 to −0.01) in the non-paretic femoral neck. A follow-up length exceeding six months was associated with a more pronounced decrease compared to a follow-up of under six months (MD, −0.08; 95% CI, −0.11 to −0.05 vs MD, −0.04; 95% CI, −0.06 to −0.02; P =  0.03). No significant change in lumbar spine BMD was detected post-stroke (MD, −0.00; 95% CI, −0.03 to 0.02), nor was significant change observed in the non-paretic distal radius, proximal humerus, tibia, trochanter, and total hip. Stroke was not associated with an increased risk of osteoporosis or osteoporotic fractures (HR, 1.43; 95% CI, 0.95-2.13). Conclusion: Stroke survivors undergo significant BMD loss in paralyzed limbs, most notably in the femoral neck. However, BMD in the lumbar spine does not exhibit a significant decrease post-stroke. The risk of post-stroke osteoporosis or osteoporotic fractures should be interpreted with caution and needs further investigation.